The Association of the Neutrophil-Lymphocyte Ratio With Diabetes Mellitus and Diabetic Foot Ulcer: A Review Article - Sylvana, Dhini; Santi Syafril (TALENTA Publisher, Universitas Sumatera Utara, 2022)
Introduction: Diabetes mellitus (DM) is inappropriately elevated blood glucose levels. Diabetic foot ulcer (DFU) is the most common complication of diabetes mellitus. Many research studies was found that neutrophil lymphocyte ratio (NLR) have positive correlation with HBA1C, blood glucose, and outcome of diabetic foot ulcer. Methods: The literature searches using online databases such as PubMed, ScienceDirect Elsevier, and Google Schoolar. Result: After doing an online search, we found 39 articles were relevant for this review topic. Analysis: Many research studies have found increased HbA1C (≥6,5) and increased blood glucose (random blood glucose ≥ 200mg/dL and/or fasting blood glucose ≥126 mg/dL) in patients with diabetes mellitus have a positive correlation with increased NLR. And there was increased NLR values in patients with diabetic foot ulcer and NLR values was higher (NLR≥6) in non-healing ulcers than in healing ulcers. Conclusion: NLR can be used as screening tool for determining evaluation of diabetes mellitus and as screening tool for determining outcome of diabetic foot ulcers.